MiNDSTEp differential photometry of the gravitationally lensed quasars WFI2033-4723 and HE0047-1756: microlensing and a new time delay - Giannini, Emanuela; Schmidt, Robert W.; Wambsganß, Joachim; Proft, Svea; Schönebeck, Frederik (Arxiv, 2016)
We present V and R photometry of the gravitationally lensed quasars WFI2033-4723 and HE0047-1756. The data were taken by the MiNDSTEp collaboration with the 1.54 m Danish telescope at the ESO La Silla observatory from 2008 to 2012. Differential photometry has been carried out using the image subtraction method as implemented in the HOTPAnTS package, additionally using GALFIT for quasar photometry. The quasar WFI2033-4723 showed brightness variations of order 0.5 mag in V and R during the campaign. The two lensed components of quasar HE0047-1756 varied by 0.2-0.3 mag within five years. We provide, for the first time, an estimate of the time delay of component B with respect to A of $Δ t= 7.6±1.8$ days for this object. We also find evidence for a secular evolution of the magnitude difference between components A and B in both filters, which we explain as due to a long-duration microlensing event. Finally we find that both quasars WFI2033-4723 and HE0047-1756 become bluer when brighter, which is consistent with previous studies.
Gesehen am 26.10.2017